Molecular Targets of Omega 3 and Conjugated Linoleic Fatty Acids – “Micromanaging” Cellular Response - Visioli, Francesco; Giordano, Elena; Nicod, Nathalie M.; Davalos, Alberto (Frontiers in Physiology, 2012)
Essential fatty acids cannot be synthesized de novo by mammals and need to be ingested either with the diet or through the use of supplements/functional foods to ameliorate cardiovascular prognosis. This review focus on the molecular targets of omega 3 fatty acids and CLA, as paradigmatic molecules that can be explored both as nutrients and as pharmacological agents, especially as related to cardioprotection. In addition, we indicate novel molecular targets, namely microRNAs that might contribute to the observed biological activities of such essential fatty acids.